Influence De La Bancarisation Et Du Credit Bancaire Sur La Croissance Economique Dans La Zone Cemac - Armand Gilbert, Noula; Nguemnang Y. Rodrigue, Bkwayep; Fokwa ArsÃ¨ne, Mba (European Scientific Journal, ESJ, 2016)
The CEMAC countries have decided to develop the banking sector to ensure economic growth48 for a sustainable development, given that the banking system leads to investments. Our study aims at analyzing the influence of bank credit and banking rate on economic growth in the CEMAC zone from time series data during 1980-2014 (CD -ROM, WBI- 2014). The econometric analysis that we have chosen was inspired by the generalized least squares method. The model we preferred was that of Hague (2000) where the Gross Domestic Product is the dependent variable for assessing the level of economic growth while the bank credit and the banking rate are the main explanatory variables. The results indicate that the variables are significant thus, the banking rate affects economic growth positively. Following these results one could think about new strategies that will help increase the banking rate which is still very low in the Sub-region.